«Bleu, saignant, à point, bien cuit»: la relació entre el cos i el menjar en les poetes catalanes. - MATAS REVILLA, MERITXELL (Scripta)
The link between corporeality and the semantic field of food -which includes foodstuff, digestive processes, organs and eating disorders- is of particular relevance for the study of 21st century Catalan poetics. Catalan poets examine aspects as diverse as the tension between desire and hunger for the creation of the Other, eroticism and sexuality, canons of beauty and gender roles and dirt and abjection. The studies of Silvia Tubert, Raquel Santiso, Mari Luz Esteban, Domenico Cosenza and Naomi Wolf provide the theoretical framework on which we interpret how these authors articulate different expressions of the intersections between body and food. The poets studied are Noa Noguerol, Maria Sevilla, Anna Gas, Maria Isern, Mireia Calafell, Lucia Pietrelli, Irene Solà and Núria Pujolàs.